Duration of preclinical, prodromal, and dementia stages of Alzheimer's disease in relation to age, sex, and APOE genotype. Issue 7 (1st June 2019) - Vermunt, Lisa; Sikkes, Sietske A.M.; van den Hout, Ardo; Handels, Ron; Bos, Isabelle; van der Flier, Wiesje M.; Kern, Silke; Ousset, Pierre‐Jean; Maruff, Paul; Skoog, Ingmar; Verhey, Frans R.J.; Freund‐Levi, Yvonne; et al.
Abstract: Introduction: We estimated the age‐specific duration of the preclinical, prodromal, and dementia stages of Alzheimer's disease (AD) and the influence of sex, setting, apolipoprotein E ( APOE ) genotype, and cerebrospinal fluid tau on disease duration. Methods: We performed multistate modeling in a combined sample of 6 cohorts (n = 3268) with death as the end stage and estimated the preclinical, prodromal, and dementia stage duration. Results: The overall AD duration varied between 24 years (age 60) and 15 years (age 80). For individuals presenting with preclinical AD, age 70, the estimated preclinical AD duration was 10 years, prodromal AD 4 years, and dementia 6 years. Male sex, clinical setting, APOE ε4 allele carriership, and abnormal cerebrospinal fluid tau were associated with a shorter duration, and these effects depended on disease stage. Discussion: Estimates of AD disease duration become more accurate if age, sex, setting, APOE, and cerebrospinal fluid tau are taken into account. This will be relevant for clinical practice and trial design.